A curious serendipitous finding: Spitz naevus combined with a syringoma. (4th June 2012) - Piana, Simonetta; Ragazzi, Moira; Zalaudek, Iris; Argenziano, Giuseppe
ABSTRACT: Combined tumours are often a serendipitous finding. Among the spectrum of melanocytic tumours, the co‐existence of different cell populations of the same linage is a well‐recognised phenomenon. Less commonly documented, but still well documented is the event of a melanocytic tumour in collision with an epithelial benign or malignant neoplasm. Exceptionally infrequent is however the collision of a Spitz naevus with an epithelial tumour. Here we report the clinical‐dermoscopic and histopathological findings of a Spitz naevus occurring in collision with a syringoma.